Engagement Markers in Polytechnic Students’ Personal Statements: An Appraisal Analysis of Self-Representation - Latipah, Yeni; Parhani, Fajrin Mubarokah; Sundawati, Fitri Hidayah (IKIP Siliwangi, 2025)
This study investigates how polytechnic students construct self-representation in personal statements through the lens of the Engagement marker of Appraisal Theory. Drawing on Martin and White’s (2005) framework, the research analyzes 25 personal statements written by first-year Engineering Technology Management students at a public polytechnic in West Java. Using qualitative methods and corpus-assisted analysis via the UAM Corpus Tool, this study identifies a dominant reliance on monoglossic assertions, with 64% of clauses presenting information as uncontested truths. While such statements convey confidence and clarity, they often lack dialogic Engagement and rhetorical nuance. Heteroglossic resources, namely disclaim, proclaim, entertain, and attribute strategies, appear less frequently but provide critical insights into the students’ efforts to enhance credibility, show self-awareness, and align with institutional expectations. This study adds to the expanding literature on L2 academic writing by emphasizing the importance of dialogic positioning in persuasive self-representations.